MATEMÁTICAS EN CUBA: ENSEÑANZA, INVESTIGACIÓN, AVANCES Y RETOS. Una visión en el contexto de América Latina - Alvarez Díaz, Lilliam (2025)
This article does not intend to be exhaustive, but to offer and share with readers an overview that reflects what the Teaching of Mathematics in Cuba is like, providing reflections on the context, achievements, obstacles and deficiencies still to be overcome. Not everything has been progress, many challenges still remain, although good results and successes have also been achieved that are shared in this text. This contribution presents aspects ranging from the training of Mathematics teachers for more than 6 decades, the attention to children with talents, to the multiple actions and achievements in the teaching of Mathematics outside the School, through extra-curricular channels. Although in Cuba, and it is fair to recognize this, there has been progress in the midst of a complicated context and global and internal crises, there is still much to be done and shared, especially in the Central American and Caribbean regions.